2002
DOI: 10.1084/jem.20012088
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of LIGHT-HVEM Costimulation Prolongs Cardiac Allograft Survival

Abstract: LIGHT (TNFSF14), a tumor necrosis factor superfamily member expressed by activated T cells, binds to herpes virus entry mediator (HVEM) which is constitutively expressed by T cells and costimulates T cell activation in a CD28-independent manner. Given interest in regulating the effector functions of T cells in vivo, we examined the role of LIGHT-HVEM costimulation in a murine cardiac allograft rejection model. Normal hearts lacked LIGHT or HVEM mRNA expression, but allografts showed strong expression of both g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 25 publications
5
86
1
Order By: Relevance
“…Moreover, T cell induction of B7-H3 enhances TCR-driven CD4 and CD8 cell activationinduced proliferation in vitro and in vivo. These data extend the concept of APC-expressed B7-H3 ligating an as yet unknown receptor on T cells and promoting T cell responses, and move B7-H3 into the same functional category as LIGHT [24], i.e. both B7-H3 and LIGHT are inducible molecules on T cells which can ligate cognate receptors and costimulate T:T cell activation.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Moreover, T cell induction of B7-H3 enhances TCR-driven CD4 and CD8 cell activationinduced proliferation in vitro and in vivo. These data extend the concept of APC-expressed B7-H3 ligating an as yet unknown receptor on T cells and promoting T cell responses, and move B7-H3 into the same functional category as LIGHT [24], i.e. both B7-H3 and LIGHT are inducible molecules on T cells which can ligate cognate receptors and costimulate T:T cell activation.…”
Section: Discussionsupporting
confidence: 70%
“…Since the presence or absence of B7-H3 affected T celldependent host responses in several allograft models, we also considered whether B7-H3 might be expressed by host T cells in addition to APC and thereby contribute directly to T cell alloresponses in the same way as certain other T:T costimulatory pathways, such as LIGHT and herpes virus entry mediator (HVEM) [24]. Analysis by flow cytometry indeed showed that both CD4 and CD8 T cells activated by TCR stimulation using CD3 mAb alone up-regulated B7-H3 expression, but peak expression required both CD3 and CD28 costimulation (Fig.…”
Section: B7-h3 Expression By T Cells In Vitromentioning
confidence: 99%
“…Mice deficient in LIGHT show defects in lymph node architecture and reduced cytotoxicity of CTLs. 25,26 In addition, LIGHT has been demonstrated to induce the expression of various chemokines and adhesion molecules that favor the infiltration of lymphocytes into tumor tissues. 19 Interestingly, a recent study showed that LIGHT is constitutively expressed in some human melanoma cells and tumor-derived microvesicles and that tumors expressing LIGHT were associated with increased lymphocytic infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the first question, LIGHT knockout mice showed enhanced cardiac allograft survival using the same model as used in the current studies, and use of HVEM-Ig in WT recipients also prolonged survival (25). These data were interpreted as showing the importance of the LIGHT/HVEM pathway in T cell costimulation, though in retrospect a role for HVEM-Ig binding to BTLA and promoting negative signals within T cells may also have contributed.…”
Section: Discussionmentioning
confidence: 55%